PENGARUH KONSENTRASI CHITOSAN SEBAGAI BAHAN PENGAWET TERHADAP MASA SIMPAN MIE BASAH - Wisnu Satyajaya; Otik Nawansih (Jurnal Teknologi & Industri Hasil Pertanian, 2008)
The objective of this research was to asses the optimal chitosan concentration as wet noodle preservative. The study conducted two stage 1) . to know the best concentration and storage duration of wet noodle.  The first factor was chitosan concentration (K) K0 (0 ppm), K1 (50 ppm), K2 (100 ppm), K3 (150 ppm), K4 (200 ppm) and the second factor was storage duration H0 (0 hour),  H1( 24 hours), H2 (48 houurs) and H3 (72 hours).  2). To know the best chitosan  concentration’s  compared with using of formalin. The result shows that higher chitosan concentration will give higher quality wet noodle which was showed by parameter microba total account, texture, rancidity, and overall acceptance. Optimal chitosan concentration was 150 ppm  with  optimal storage duration  24 hours. Chitosan can be developed  and  used to avoid formalin and the other kinds of  hazard material using for food product. Keywords : Chitosan, formalin. antibacterial activities